Hubungan Komunikasi Orang Tua dengan Keputusan Karir Siswa SMA Islam Az-Zahrah Palembang - Nopa Romadalia, Riski; Lubis, Khadijah; Novirson, Rizki (Program Studi Bimbingan dan Konseling FKIP UMSU, 2025)
Every student is faced with the demand to determine a career direction that aligns with their potential and interests. However, in the process of making career decisions, students confusion and need support from their closest environment, especially their parents. Effective communication between parents and children plays an important role in providing guidance, motivation, and information related to career choices. Based on this, the study aims to determine the relationship between parental communication and students’ career decision-making of students. This research with correlational studies with 218 students as sample. Data were collected using the parental communication scale and the career decision-making scale, each consisting of 40 items. Data analysis was conducted using the Pearson Product Moment correlation test with the help of SPSS version 22. The results showed a correlation coefficient of r = 0.578 with a significance value of p = 0.000 0.05, indicating a positive and significant relationship between parental communication and students’ career decision-making. These findings suggest that the better the communication established between parents and children, the better students are in making appropriate career decisions. Thus, parental communication plays an important role in helping students prepare for and determine their future career paths.